Finding, reading, and using the law - Anne M. Stevens (West/Thomson Learning, 2002)
This new book is an excellent resource for the paralegal or legal assistant. It approaches legal research, analysis and communication, simply and enjoyably. Exercises based on realistic case materials guide readers in their own legal research, verification, analysis and advocacy. The book includes a glossary, index and legal citation rules summary. Sample legal documents and additional exercises (with answers) are found on the enclosed disk and are perfect for self-review